A Community-Engaged Research (CEnR) to Explore Attitudes, Behaviours, and Experiences (CABE) of Men Who have Sex with Men (MSM) and Transgender Women (Waria) in Bali, Indonesia. - Septarini, Ni Wayan (Curtin University, 2022)
The CABE project is a community-engaged research study exploring attitudes, behaviours, and experiences of men who have sex with men (MSM) and transgender woman (waria) in Bali, Indonesia. The mixed methods study comprises five phases and explores sexual health attitudes, behaviours, and experiences of MSM and waria. Enablers and barriers of safe sex behaviours were explored and recommendations for interventions to improve safer sex behaviours among MSM and waria in Bali have been made.